PEMBERDAYAAN PRODUKTIVITAS REMAJA MELALUI AQUAPONIC SEBAGAI WUJUD KREATIFITAS MASYARAKAT DI DUSUN DAWUHAN DESA KAYUGIYANG WONOSOBO - Ulfa Husnafisaadah; Muhammad Naufal Izzulhaq; Siti Robiah Adawiyah; Fida Nur Fauziah; Elma Esti H; Khoerul Khafifudin; Umi Rofiqoh; Alman Sulaiman Q; Ade Lofalian; Azka Al Aza; Ulfah Taufika Kh (Pusat Riset dan Inovasi Nasional, 2022)
The Community Service Lecture work program in the form of hydroponic kale and catfish cultivation applications with an aquaponic system was carried out in Dawuhan Hamlet, Kayugiyang Village, Wonosobo Regency. The purpose of this KPM work program is to utilize the yard of the house so that it has productive value and educate the community with environmentally friendly cultivation systems. The stages of implementing this work program include the stages of field surveys and partner conditions, seeding kale seedlings, installing Aquaponics installation ponds, and mentoring activities. The technology used is the aquaponic system cultivation, which utilizes catfish manure as natural fertilizer for water spinach plants placed on it. From the results of the implementation of the KPM work program, it resulted in 1 (one) unit of aquaponic cultivation ponds, increasing public knowledge, especially for teenagers who are KPM partners.